Effects of neutral polysaccharide from Platycodon grandiflorum on high-fat diet-induced obesity via the regulation of gut microbiota and metabolites - Song, Jing; liu, Qin; Hao, Mengqi; Zhai, Xiaohu; Chen, Juan (Frontiers in Endocrinology, 2023)
Graphical Abstract